An epidemiological survey of rheumatic fever and rheumatic heart disease in Sahafa Town, Sudan. Issue 5 (October 1992) - Ibrahim-Khalil, S; Elhag, M; Ali, E; Mahgoub, F; Hakiem, S; Omer, N; Shafie, S; Mahgoub, E
Abstract : STUDY OBJECTIVE–The aim was to determine the prevalence of rheumatic fever and rheumatic heart disease and to initiate a programme of secondary prophylaxis in Sahafa Town, Sudan. DESIGN–The study was a prospective case finding survey, carried out by a specially trained team headed by a cardiologist. SETTING–The study involved high risk school children (5-15 years of age) from Sahafa Town in the period 1986-1989. SUBJECTS–A total of 13, 332 children on the school registers (7892 boys and 5430 girls) were examined generally and specifically for evidence of rheumatic fever or rheumatic heart disease. MAIN RESULTS–Out of the 13, 322 children screened 351 were suspected cases and 146 were confirmed cases of rheumatic fever or rheumatic heart disease. The prevalence rates for all ages were 10/1000 for boys and 14/1000 for girls. The overall prevalence rate of the whole programme area was 11/1000, prevalence of rheumatic fever was 8/1000, and prevalence of rheumatic heart disease was 3/1000. The prevalence rate was significantly increased among the inner town inhabitants (15/1000) compared to the outer town inhabitants 4/1000 (p < 0.001). Monthly prophylactic benzathine penicillin in a dose of 1, 200, 000 IU was given to both suspected and confirmed cases. Penicillin coverage rate was 72%. CONCLUSIONS–Rheumatic fever continues to be a serious health problem. With economic pressures causing impending change in socioeconomic conditions in most Third World countries in the immediate future, rheumatic fever will continue to have a high prevalence rate and rheumatic fever and rheumatic heart disease prevention programmes will remain a central goal.